Olfactory neurogenesis plays different parts at successive stages of life, implications for mental health - Dejou, Jules; Mandairon, Nathalie; Didier, Anne (Frontiers in Neural Circuits, 2024)
The olfactory bulb is a unique site of continuous neurogenesis, primarily generating inhibitory interneurons, a process that begins at birth and extends through infancy and adulthood. This review examines the characteristics of olfactory bulb neurogenesis, focusing on granule cells, the most numerous interneurons, and how their age and maturation affect their function. Adult-born granule cells, while immature, contribute to the experience-dependent plasticity of the olfactory circuit by enabling structural and functional synaptic changes. In contrast, granule cells born early in life form the foundational elements of the olfactory bulb circuit, potentially facilitating innate olfactory information processing. The implications of these neonatal cells on early life olfactory memory and their impact on adult perception, particularly in response to aversive events and susceptibility to emotional disorders, warrant further investigation.This review examines the characteristics of olfactory bulb neurogenesis, focusing on granule cells and how their age and maturation affect their function. It explores the role of adult-born granule cells in experience-dependent plasticity and the foundational role of neonatal granule cells in olfactory information processing. The implications for adult perception, early life olfactory memory, and susceptibility to emotional disorders are also considered.